Photobiomodulator Effect on Fibromyalgia Stabilization in the Oncoterapeutic Process (Global Journal of Medical Research, 2018)
In this case study, Photobiomodulation was used in the craniofacial and systemic region for the symptomatic control in patients with Fibromyalgia (fibrositis syndrome or fibromyositis), simultaneously with oncoterapic therapy through the specific hormone (Tamoxifen-TMX). This non-invasive and low-cost planning emerges as an alternative in the systemic recovery of patients with this syndrome at Hospital of Câncer de Ribeirão Preto.
Keywords: fibromyalgia; photobiomodulation; laser therapy; oncology; cancer; dentist; hormone